IMPLEMENTASI INOVASI CILOK TEMPE SEBAGAI PEMBERIAN MAKANAN TAMBAHAN ( PMT ) DALAM UPAYA PENCEGAHAN STUNTING DI POSYANDU BOUGENVILLE DESA BOJONG NANGKA - Fika Ardyani Elmenes; Arin Khairunnisa (SINERGI : Jurnal Riset Ilmiah, 2026)
stunting is a chronic nutrional issue that remains a major concern in Indonesia due to its impact on children ‘s physical growth and cognitive development. This condition is generally caused by a long-term lack of nutrional intake, particularly during the first 1,000 days of life. One preventive measure that can be taken is providing supplementary feeding ( PMT ) that is not only nutritious but also affordable and easily accepted by toddlers. This study aims to implement a local food innovation in the form of “ cilok tempe “ ( tempeh starch ball ) as an alternative PMT at Bougenville Posyandu in Bojong Nangka Village. The method used is descriptive with a participatory approach throught educational activities and direct practice with mothers of toddlers. The result showed that 87% of toddlers accepted the product well, and there was a 25% increase in mothers ‘s understanding of the importance of balanced nutrition based on a comparison of pre-test and post – test result. The “ cilok tempe “ innovation is proven to be an economical and nutritious PMT alternative with he potential to be replicated at the community level.